Latent hardening effect under self- and coplanar dislocation interactions in Mg single crystals. (September 2015) - Hiura, F.; Niewczas, M.
Abstract : Latent hardening experiments were carried out on Mg single crystals under basal self- and coplanar dislocation interactions. For self-interactions the latent hardening ratio ( LHR ) is independent on the amount of primary deformation in the basal slip system. For coplanar interactions LHR increases linearly with primary strain and quadratically with primary stress, suggesting that during the stage A in Mg the coplanar slip systems harden proportionally to the dislocation density accumulated in the other coplanar slip system.